82 THE IMPACT OF THE COVID-19 PANDEMIC ON THE ACTIVITY OF A RAPID-ACCESS GERIATRIC DAY HOSPITAL SERVICE. (25th October 2022) - Moloney, K; Byrne, T; Mathews, S; Foran, M; Conroy, B; Molamphy, A; Murphy, N; Dillon, A; Doyle, K; Cunningham, C; Romero-Ortuno, R
Abstract: Background: In the 1970s, Jack Flanagan developed the first Geriatric Day Hospital (GDH) in Ireland. Since, the GDH model of care has evolved to accommodate for the growing demands of our ageing population. Before the COVID-19 pandemic, the operational scope of our GDH was extended to allow for the rapid medical and multidisciplinary assessment and follow-up of older patients. During the pandemic, the GDH did not suspend operations and remained open as a COVID-negative ambulatory pathway. We evaluated the activity of this GDH service. Methods: Retrospective Service Evaluation Approval was granted by our Research & Innovation Office (Reference: 7419). Pseudonymised data corresponding to all GDH attendances between January 2017 and December 2021 were retrieved from the hospital electronic records. Yearly trends in proportions were tested with the Chi-square for trend statistic. Trends in monthly attendances were assessed via Statistical Process Control (SPC) charts with three-sigma limits. Statistical significance was set at p<0.05. Results: There were 27, 278 attendances of patients aged 65 and over to the GDH over the 5-year period (6, 362, 5, 978, 6, 115, 4, 306, and 4, 517, respectively). Mean age was 82 every year. Of the 7, 813 new episodes, yearly proportions referred directly by primary care teams were 10.4%, 29.5%, 38.6%, 24.5%, and 16.3% (p<0.001). SPC charts showed that Apr-May 2020 and Jan-Feb 2021 had significantly lower numbers of review attendances (50-59 and 146-142, respectively, average 324 p/m). However, new appointments did not significantly decline (average 130 p/m). Of the 7, 813 new episodes, 2, 595 (33.2%) were seen by Physiotherapy, and 1, 860 (23.8%) by Occupational Therapy. Conclusion: Our GDH saw a sustained number of new attendances and demonstrated increased community availability during the unprecedented COVID-19 crisis, especially during the first wave of the pandemic when hospital access was most affected. A rapid access GDH model can facilitate integrated care at times of crisis to promote ageing in place.